High dose chemotherapy and autologous stem cell transplantation in nodular lymphocyte‐predominant Hodgkin lymphoma: A retrospective study by the European society for blood and marrow transplantation‐lymphoma working party. Issue 1 (9th November 2017) - Akhtar, Saad; Montoto, Silvia; Boumendil, Ariane; Finel, Herve; Masszi, Tamas; Jindra, Pavel; Nemet, Damir; Fuhrmann, Stephan; Beguin, Yves; Castagna, Luca; Ferrara, Felicetto; Capria, Saveria; et al.
Abstract: Whilst autologous stem cell transplantation (auto‐SCT) is considered standard of care for relapsed/refractory classical Hodgkin lymphoma, the role of auto‐SCT in nodular lymphocyte‐predominant Hodgkin lymphoma (NLPHL) is not well defined due to limited data. We report the first study on auto‐SCT for NLPHL with a larger cohort. Eligible for this retrospective registry study were patients reported to the EBMT between 2003 and 2013, aged 18 or older with relapsed/refractory NLPHL who underwent first auto‐SCT with disease chemosensitive to salvage therapy. NLPHL transformed to diffuse large B cell lymphoma were excluded. Sixty patients (83% male; median age 40 years) met the eligibility criteria. The median time between diagnosis and transplant was 21 months (IQR 13–58), and the median number of prior treatment lines was 2 (range 1–5), including rituximab in 63% of the patients. At auto‐SCT, 62% of the patients were in complete remission (CR) and 38% in partial remission. Seventy‐two percent of the patients received BEAM as high‐dose therapy. With a median follow‐up of 56 months (range 3–105), 5‐year progression‐free and overall survival (OS) were 66% and 87%, respectively. Univariate comparisons considering age, time from diagnosis to transplant, prior chemotherapy lines, and prior rituximab use failed to identify significant predictors for any survival endpoint except for being in CR at the time of auto‐SCT (vs PR, P  = .049) for OS. Auto‐SCT in patients with relapsed/refractory NLPHL who are sensitive to salvage therapy gives excellent disease control and long‐term survival independent of the time interval between diagnosis and transplant.